The Relationship Between Work Motivation and Work Engagement in BBPPKS Banjarmasin Employees - Safitri, Iti; Musfichin; Mulyani (Indonesian Academy of Social and Religious Research (IASRR), 2024)
The purpose of this study was to determine the relationship between work motivation and work engagement in employees of the Banjarmasin Social Welfare Education and Training Center. The research method used is quantitative method with correlational type. The population and sample were 27 people. Sampling using non-probability sampling technique with saturated sampling type. The data collection technique in this study used a Likert scale, namely the work motivation scale and work engagement assisted by the SPSS version 26 application. The results of this study indicate that the p value = 0.000 <0.05, so it can be concluded that there is a significant positive relationship between work motivation and work engagement variables. This means that the higher the work motivation, the higher the work engagement of a person.